Synthesis and Characterization of Janus Magnetic Nanoparticles and its Application as an Adsorbent (Journal of Chemical Engineering, 2013)
A simple and quick method to synthesize Janus magnetic particles in the nano-sized range was conducted. Magnetic nanoparticles (MNPs) with diameters in the range of 10-15 nm were prepared by the co-precipitation of Fe2+ and Fe3+ precursors under alkaline and inert condition. The Pickering Emulsion method was used for the immobilization of magnetic nanoparticles onto the surface of paraffin wax balls via water-molten wax emulsion. Silanization of the exposed side of the immobilized magnetic particles was carried out with APTES and the waxes were subsequently dissolved to obtain free Janus nanoparticles. Characterization tests such as TGA, SEM-EDX, TEM and FTIR were performed to ascertain the partial coating of the Janus nanoparticles. Moreover, adsorption capacity of the Janus nanoparticles on Hg2+ ions was found to be intermediate between those using the uncoated and fully coated nanoparticles indicating successful synthesis of Janus nanoparticles DOI: http://dx.doi.org/10.3329/jce.v27i1.15861 Journal of Chemical Engineering, IEB Vol. ChE. 27, No. 1, June 2012: 64-68